2008
DOI: 10.3354/meps07201
|View full text |Cite
|
Sign up to set email alerts
|

Diet and feeding intensity of sardine Sardina pilchardus: correlation with satellite-derived chlorophyll data

Abstract: Spatio-temporal variability of the diet of sardine Sardina pilchardus off Portugal was examined through analysis of the stomach contents of fish collected every 14 d from the west and south of Portugal during 2003Portugal during /2004. Dietary composition of the modal sardine length class was assessed by determining the frequency of occurrence and carbon content of identified prey, and these 2 parameters were combined to estimate a modified index of relative importance of prey (mIRI). The most important prey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
101
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 31 publications
12
101
1
Order By: Relevance
“…The observed seasonal alternations of allometric condition factor and fullness index additionally confirmed that sardines were in the best condition at the beginning of the spawning season, for which they prepared themselves by higher feeding intensity, leading to higher storage of consumed energy. However, this should be further investigated, as in upwelling areas (Garrido et al, 2008) diet seasonality might be linked not only to the reproduction cycle but also to some other environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed seasonal alternations of allometric condition factor and fullness index additionally confirmed that sardines were in the best condition at the beginning of the spawning season, for which they prepared themselves by higher feeding intensity, leading to higher storage of consumed energy. However, this should be further investigated, as in upwelling areas (Garrido et al, 2008) diet seasonality might be linked not only to the reproduction cycle but also to some other environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Sardine is a batch spawner with indeterminate fecundity (Blaxter and Hunter, 1982;Ganias et al, 2003). According to the existing sardine diet-related information, it is evident that sardine feeding preferences or mode (filter or particulate feeding) largely depend on the environmental conditions of the region from which it originated (Garrido et al, 2007(Garrido et al, , 2008Costalago et al, 2015). Nevertheless, omnivory in the sardine is well documented worldwide (Navarro, 1952;Cunha et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although phytoplankton has been found to contribute significantly to the diet of the 2 species in certain areas/conditions (e.g. James 1987, Garrido et al 2008, it is well established that the bulk of their dietary carbon is of zooplanktonic origin (e.g. James 1987, van der Lingen et al 2006, Espinoza & Bertrand 2008, Garrido et al 2008, Espinoza et al 2009, Nikolioudakis et al 2012.…”
Section: Dietmentioning
confidence: 99%
“…SPF are omnivorous planktivores, able to switch between filter-and particulate feeding modes (James 1987, van der Lingen et al 2006, Garrido et al 2007, and they derive the bulk of their dietary carbon from zooplankton, mainly copepods and euphasuiids (e.g. Garrido et al 2008, Espinoza & Bertrand 2008, Espinoza et al 2009, Nikolioudakis et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Garrido et al (2007Garrido et al ( , 2008 described both the feeding behaviour of sardines under culture conditions, and the diet and food intensity in the wild. However, none of these studies has focused on long-term growth in captivity.…”
Section: Introductionmentioning
confidence: 99%